The influence of WICS model, courage and self-efficacy on effective leadership: A military perspective / Mohamad Rudi Othman - Mohamad Rudi , Othman (2020)
Effective leadership is complex; however, its application is always critical especially for military organisations. In grasping effective leadership, the Malaysian Army always emphasises continuous leadership training towards its leaders. The Army doctrines guide training in the Malaysian Army, a manual specifically formulated to suit the service requirement. Correspond to leadership scholars and researchers, the Army believed effective leaders possess a set of virtues that differentiate them from non-leaders and these virtues could be developed. The leadership training in the Army begins as early as when an officer report for basic officer cadet training and the training continues progressively as officers climb-up their career ladder. Positive virtues are developed accordingly. Nevertheless, few empirical studies had been conducted on the kind of virtues that really associates with effective military leadership. Hence, this research is examining virtues from effective leadership model and the one specified in the Army doctrines. Consequently, a WICS (an acronym for Wisdom, Intelligence, and Creativity Synthesised) were found in the literatures, while Courage and Self-efficacy were found from the Army in-house context. An extensive research instrument was adopted to rationalise measuring processes. Hence, the virtues were empirically tested on the Army senior-level officers who have undergone the highest leadership training scheme recognised as the Malaysian Armed Forces Defence College Course (MAFDC). Concurrently, senior officers who graduated from the course will be awarded with a Master degree and assume strategic level leadership appointment in the Malaysian Armed Forces. There were 201 of them available for this research and 91 responded to the survey. The research deploys SmartPLS version 3.0 to analyse all data. The result of this research suggested that wisdom and self-efficacy are virtues that have a significant relationship with effective military leadership while emotional intelligence, creativity and courage were not. Nevertheless, emotional intelligence, creativity and courage were mediated by self-efficacy in further describing effective military leadership. The findings of this study have managed to provide a new useful paradigm for the Malaysian Army in multiple directions. Firstly, the human resource department may use the results as a consideration in their periodically reviewed leaders’ development planning. The second direction involves the Army training institutions that may consider the development of those virtues in their training program. Indeed, further brainstorming sessions would translate the virtues into appropriate training scheme. As the third direction, the study provided a fresh platform for more empirical studies to be conducted especially in the same field but different in paradigm and perspective. Fourthly, the effort has played its part as a contributor to the body of knowledge. One must remember that this research was conducted in Malaysian Army senior-level leaders setting and the result may differ if used in another context. The study opens up future research opportunities and these were explained in the final chapter of the research